Surgical alternative for maxillary sinus approach in the post maxilla. Case Report. - Flores Ortiz, Washington Javier (2020)
The present case is about a 25-year-old male patient, with no relevant medical history, who attended the SERODU dental clinic. On clinical examination, it is observed that the patient presents sensitivity when making a light tapping of the lateral wall of the left maxillary sinus externally on the cheekbones and intraoral palpation on the lateral surface of the maxilla between the canine and zygomatic fossa. In the tomographic study, a hypodense image compatible with an infectious process and a hyperdense image related to a root remnant belonging to a dental organ No. 2.6 is observed. The objective of this study is to describe the clinical case of a patient with sinusitis of odontogenic origin due to displacement of a radicular remainder towards the left maxillary sinus, in which clinical and surgical procedures were performed through trepanation in the post maxilla, which obtained greater precision. for foreign body removal compared to the classic Caldwell Luc approach. 8 days after the surgical procedure, the stitches were removed and optimal soft tissue healing, absence of pain, edema, and infection was observed clinically. Tomographic control was carried out three months after the intervention to assess the results of the treatment and to follow up the case. The surgical approach carried out constitutes an invasive and effective treatment for the removal of root remains.